2017
DOI: 10.1016/j.bandl.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Tone-grammar association within words: Concurrent ERP and fMRI show rapid neural pre-activation and involvement of left inferior frontal gyrus in pseudoword processing

Abstract: Using a concurrent ERP/fMRI paradigm, we investigated how listeners take advantage of morphologically relevant tonal information at the beginning of words to predict and pre-activate likely word endings. More predictive, low tone word stems gave rise to a 'pre-activation negativity' (PrAN) in the ERPs, a brain potential which has previously been found to increase along with the degree of predictive certainty as regards how a word is going to end. It is suggested that more predictive, low tone stems lead to rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
2
12
2
Order By: Relevance
“…The RAM is compatible with the neural imaging evidence suggesting a multi-level cortical network for tone processing (Roll et al, 2015;Shuai and Malins, 2016;Si et al, 2017;Soderstrom et al, 2017;Schremm et al, 2018) and offers a mechanism for the suggested network dynamics to unfold. The top-down reactivation of the phonological network provides a simple mechanism for top-down factors to interact with bottom-up processing (Shuai and Gong, 2014).…”
Section: Theory the Reverse Accessing Modelsupporting
confidence: 80%
See 2 more Smart Citations
“…The RAM is compatible with the neural imaging evidence suggesting a multi-level cortical network for tone processing (Roll et al, 2015;Shuai and Malins, 2016;Si et al, 2017;Soderstrom et al, 2017;Schremm et al, 2018) and offers a mechanism for the suggested network dynamics to unfold. The top-down reactivation of the phonological network provides a simple mechanism for top-down factors to interact with bottom-up processing (Shuai and Gong, 2014).…”
Section: Theory the Reverse Accessing Modelsupporting
confidence: 80%
“…Accumulating evidence suggests that perception of tone in speech involves a complicated, multi-level cortical network (Shuai and Gong, 2014;Roll et al, 2015;Si et al, 2017;Soderstrom et al, 2017;Schremm et al, 2018). For example, event-related potential (ERP) studies (Shuai and Gong, 2014) indicate temporally overlapping but spatially separate top-down, linguistic processing and bottom-up, auditory processing of lexical tones with linguistic processing lateralized toward the left hemisphere and auditory processing toward the right hemisphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous studies (Ding et al, 2014;Dong, Huang, & Du, 2012;Feng et al, 2013) have claimed, temporal areas are involved in audio-visual processinga function that is frequently activated during screen media activity like computer and Internet use. It has been suggested that long-term hyperactivity in such regions could lead to impaired auditoryvisual abilities (Ding et al, 2014), language-processing impairment (Söderström, Horne, Mannfolk, van Westen, & Roll, 2017), and learning problems (Cone-Wesson, 2005). The negative relationship between impulsivity and the thickness of the left POrb observed in the whole sample could lend further support to the possible involvement of language processing.…”
Section: The Distinctive Connection Between Trait Impulsivity and Cormentioning
confidence: 95%
“…However, this contrasting pattern was only observed in PP bilinguals. The left insula plays a key role in articulation, speech production, or motor processing (Chang, Yarkoni, Khaw & Sanfey, 2012, Carota, Kriegeskorte, Nili & Pulvermüller, 2017, Söderström, Horne, Mannfolk, van Westen & Roll, 2017). More reliance on this region during reading in L2 in PP bilinguals might be ascribed to the high similarity of writing systems.…”
Section: Discussionmentioning
confidence: 99%